Anterior Cruciate Ligament Reconstruction Using Bone-Patellar Tendon-Bone Autograft With Lateral Compartment Meniscectomy or Chondroplasty Does Not Lead to Decreased Return to Sport and Activity Compared With No Lateral Pathology - Sean Hazzard, P.A., M.B.A; Saoirse Connolly, B.S; Brendan Fitzgerald, B.S; Peter Asnis, M.D (Elsevier, 2024)
Purpose: To investigate the influence of lateral meniscal and cartilage pathology on the outcome after anterior cruciate ligament (ACL) reconstruction in patients who participate in pivoting sports. Methods: Using a single-surgeon patient registry, patients undergoing an anterior cruciate ligament reconstruction (ACLR) using bone-patellar tendon-bone autograft were evaluated with minimum 2-year patient reported outcomes evaluated using Marx, Tegner, Lysholm, and International Knee Documentation Committee scales. Patients were divided into 3 groups: isolated ACL surgery, ACLR with a partial lateral meniscectomy, or a ACLR with partial lateral meniscectomy and lateral compartment chondroplasty. Results: A total of 98 patients met inclusion criteria. Using the isolated ACL reconstruction group as a control, we found that Marx scores were greater in patients who additionally underwent a partial lateral meniscectomy at 1 year (P = .016). There were no significant differences between the ACL-only group and the ACL with partial lateral meniscectomy and chondroplasty group. Within the partial meniscectomy cohort comparing the patients with red-white zone tears with the patients with white-white zone tear, we found there were no significant differences when compared with the ACL-only control. There were no significant differences appreciated between groups using the International Knee Documentation Committee, Lysholm, and Tegner scales. Conclusions: ACL reconstruction using bone-patellar tendon-bone autograft with anteromedial portal drilling technique does not have any significant short-term (2-year outcome) differences in return to activity and patient-reported outcomes compared with if patients additionally have a partial lateral meniscectomy and/or lateral compartment chondroplasty. Additional partial lateral meniscectomy showed significantly greater Marx scores at 1 and 2 years' postoperatively. Level of Evidence: Level III, retrospective cohort study.